DIALEKTIKA ANTARA REALITAS DAN IDELITAS TEATER PAYUNG HITAM BANDUNG - Kurnain - (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
This Script is reflection of the trip of Payung Hitam Theater which are expressed in some manuscript, such as â€œ Menunggu Godot (1991), â€œKasparâ€ (1994-2003), and â€œ Merah Bolong Putih Doblong Hitamâ€ (1996-20080) constitute the result of stretching of Indonesia modern theater which develops from un-satisfaction feeling in viewing factual reality which exist in the society. Inheritance which develops on the Modern Theater according to Saini constitutes an effort to express collision or the conflict of values that is difficult to be separated from its artist. The script of dialectic between reality and ideality of the theater Payung Hitam basically starts from the change which is appeared by group through the show of â€œKasparâ€. â€œThe function of drama manuscript is not dominant anymore. The stage of show doesnâ€™t give exposition of story or describe characters of art figure fully and realistically. The Metaphoric happening and archaic emotion are mort showed trough body expressivity of the actor, while verbal language expression becomes more minimal. The expression of theater of this period can be seen as effort to refuse hegemony of verbal language, to refuse the linearity of the story, then to open the slices of the new discourse trough the appearance of boy artistic of the language and things personificationâ€. The peak of rebellion which is done by the group of Payung Hitam Theater is laid on â€œMerah Bolong Putih Doblong Hitamâ€,that is not anymore using of main character manuscript as reference in working. Body and expression of the players then becomes language which substitutes text verbally. For stressing the happening change, in this term is chosen one of drama which is conventional, that is â€œMenunggu Godotâ€, as a measuring tool. Keywords: Dialectic, Realistic, and Idealistic.